Yahoo Web Search

  1. Ad
    related to K
  1. Sort by

  1. -k^3 + k^2 + 2*k + 4 = -k(k^2 -k - 2) + 4 = -k(k^2 -2k + k -2) + 4 = -k[k(k-2) + 1(k-2)] + 4 = -k(k+1)(k-2) + 4 How do you want us to calculate? What...

    1 Answers · Education & Reference · 25/01/2011

  2. -k===-1k .+-7k===-8k Take the numbers to the right side by changing their signs: +6-20-2===-16 -8k===-16 ... ...................k===2 Here is a more step by step explanation: There is...

    2 Answers · Education & Reference · 08/09/2013

  3. y = k√x y' = k / 2√x Now if the given line is tangent to y = k√x then the slope of the line equals k / 2√x so k / 2√x = 5 k = 10...

    1 Answers · Education & Reference · 16/02/2010

  4. k = -3 or -1 For the general quadratic ax^2 + bx +c = f(x), "solving" means finding the...'re into Complex Numbers System Now, on to your question x^2 -kx -k+1 has a Discriminant of -7 Comparing this to ax^2 + bx +c =0 a = 1, b=-k, c = -k+1 ...

    1 Answers · Education & Reference · 03/10/2011

  5. For: aA + bB = cC + dD, K may be defined as; K = (P(C)^c * P(D...

    1 Answers · Education & Reference · 24/09/2006

  6. There is no solution. If k = 0 , the equation becomes e^(0) + 4(0) + 1 = 1 + 1 = 2 If k >...; 0 . As a result, the entire expression [ e^(-6k)+4k+1 ] > 0 when k < 0. Here's a view of part of the graph of f(k) = e...

    1 Answers · Education & Reference · 29/04/2012

  7. k shifts the graph vertically. If k is positive the graph shifts up; if k is negative it shifts...

    1 Answers · Education & Reference · 02/03/2014

  8. since (1,k) is a point on the graph of this equation, all you have to do is plug 1 in for x, and when you find y, you've found k. y = 2(1)^2 - 4(1) + 6 = 2 - 4 + 6 = 4 k = 4 that's it! ;)

    2 Answers · Education & Reference · 14/05/2012

  9. Suppose k = 1. Then you have x^(2^1) = x^2, which involves one act of ...2) = x^4, which involves two acts of squaring. If k = 3, then you have x^(2^3) = x^8, which takes three. See the pattern...

    3 Answers · Education & Reference · 24/10/2007

  10. (4/7)k + (3/2) = -1 - (7/6)k [first, let's get both k expressions on one side of the equation by ...k = -1 - 3/2 [find common denominators for (4/7)k and (7/6)k so you can add them together] (24/42)k...

    2 Answers · Education & Reference · 18/09/2010

  1. Ad
    related to K
  1. Try asking your question on Yahoo Answers